Jam’iyah Diba’iyah - Faizah Faizah; Afroh Nailil Hikmah (Al-Riwayah : Jurnal Kependidikan, 2022)
This article aims to knowing the activities of jam'iyah dhiba'iyah as a tools of character education internalizing values. Jam'iyah dhiba'iyah comes from religious Arabic literary works or old literary books but still accepted by the wider community right now. Using a qualitative descriptive method, this article examines the process of implementing jam'iyah diba'iyah activities, the form of internalizing the value of character education, also supporting and inhibiting factors. The result: this activity aims to form a muslim generation with good morals. Implementation of activities in the form of dhiba'an, mauidhoh hasanah (strengthening the character education value), implementation of punishment. The values of character education that are developed include honesty, responsibility, discipline, self-confidence, independence, curiosity, and patience. The supporting factor is in the form of a mutually proactive attitude of all members in carrying out activities. There is a partnership between parents, the community and the Jam'iyah committee. The inhibiting factor is the differences in children character and parents busyness who rarely monitor and accompany the children, so that many of them fall into a bad environment